Personalized E-Portfolio: A Dynamic Web-based Tool for Students’ Professional Growth - Muhammad Syamil bin Manaf; Wan Hussain Wan Ishak; Fadhilah Mat Yamin (Journal of Sustainable Software Engineering and Information Systems, 2025)
Background of study: Electronic portfolios (e-portfolios) have become vital tools for students to document learning and build professional identity. Yet, many existing platforms are hindered by technical complexity, limited personalization, and low engagement. Aims and scope of paper: This paper introduces a personalized e-portfolio system designed to overcome these issues by applying agile and user-centered approaches, focusing on usability and adaptability in higher education. Methods: The system was developed using HTML, CSS, JavaScript, PHP, and phpMyAdmin through six agile phases: planning, design, development, testing, deployment, and review. User needs were gathered from students and lecturers, while 30 students evaluated the system using the Website Analysis and Measurement Inventory (WAMMI) across five usability factors. Result: Usability testing showed high satisfaction. Learnability (4.47), controllability (4.22), and efficiency (4.17) scored the highest, indicating that the system is intuitive and effective. Participants valued its role in reflection and personal branding, while suggesting improvements in visual design, customization, and integration with platforms like LinkedIn. Conclusion: The study confirms that agile and user-centered design can produce an adaptable e-portfolio system that enhances students’ professional growth and provides a scalable model for higher education institutions.